Production management of Indonesian-Malaysian animation: Les’Copaque and Visinema case study - Rivalda, Reza Zulfiqar; Sukmono, Filosa Gita (ProTVF, 2026)
Background: Animation in Southeast Asia has developed rapidly, as evidenced by certain Indonesian and Malaysian animated films. However, many research that have been conducted focused mainly on animation production management within specific industries, such as film or television, without considering differences in studio size, asset lifespan, and workflow structure across productions. Purpose: This research aims to address this gap by comparing animation production management of film Jumbo at Visinema Pictures (Indonesia) with the series Upin & Ipin at Les’ Copaque Production (Malaysia). More specifically, it examines production processes in terms of originality, efficiency, and scalability. Methods: Using a qualitative case study approach, data were collected through in-depth interviews with key stakeholders, such as directors and compositors from both studios. The research was organized into three phases: pre-production, production, and post-production. Results: The results indicate that each production management puts more emphasis on content format and organizational strategy. Visinema Pictures prioritizes pre-production, emphasizing creativity in building the original story and visual elements for Jumbo. In contrast, Les’ Copaque Production utilizes existing asset collections and standardized workflows for more efficient production of Upin & Ipin series. Both studios use organized processes for production and post-production; however, Visinema prioritizes creative exploration while Les’ Copaque prioritizes long-term operational efficiency. Conclusion: This research concludes that animation production management in Southeast Asia relies on a strategic interplay between originality, efficiency, and scalability, rather than a single ideal model. Implications: The findings would contribute to comparative research on animation production management in Indonesia and Malaysia. Also, this research provides practical insights for animation studios’ productions regarding content format, target markets, and long-term sustainability.